Plant and sediment properties in seagrass meadows from two Mediterranean CO2 vents: Implications for carbon storage capacity of acidified oceans - Vizzini S.; Apostolaki E. T.; Ricevuto E.; Polymenakou P.; Mazzola A. (Marine Environmental Research, 2019)
Assessing the status of important carbon sinks such as seagrass meadows is of primary importance when dealing with potential climate change mitigation strategies. This study examined plant and sediment properties in seagrass meadows (Cymodocea nodosa (Ucria) Asch.) from two high pCO 2 –low pH Mediterranean vent systems, located at Milos (Greece) and Vulcano (Italy) Islands, providing insights on carbon storage potential in future acidified oceans. Contrary to what has been suggested, carbon content (both inorganic and organic) and its surficial accumulation decreased at high pCO 2 –low pH in comparison with controls. The decrease in inorganic carbon may result from the higher solubility of carbonates due to the more acidic conditions. At Vulcano, the seagrass properties (e.g., leaf area, biomass) appeared negatively affected by environmental conditions at high pCO 2 –low pH conditions and this may have had a detrimental effect on the organic carbon content and accumulation. At Milos, organic carbon decreased at high pCO 2 –low pH conditions, despite the increase in seagrass aboveground biomass, leaf length and area, probably as a consequence of site-specific features, which need further investigation and may include both biotic and abiotic factors (e.g., oligotrophic conditions, decreased sedimentation rate and input of allochthonous material). Results suggest that, in contrast to previous predictions based exclusively on the expected positive response of seagrasses to ocean acidification, carbon storage capacity of the seagrass C. nodosa may not increase at high pCO 2 -low pH conditions. This study emphasizes the need to investigate further the potential alteration in the climate mitigation service delivered by seagrass meadows in acidified oceans.